Age-dependent contribution of Rho kinase in carbachol-induced contraction of human detrusor smooth muscle in vitro - Kirschstein Timo; Protzel Chris; Porath Katrin; Sellmann Tina; Köhling Rüdiger; Hakenberg Oliver W (Acta Pharmacologica Sinica, 2016)
Timo KIRSCHSTEIN1,*, Chris PROTZEL2, Katrin PORATH1, Tina SELLMANN1, Rüdiger KÖHLING1, #, Oliver W HAKENBERG2, # Oscar Langendorff Institute of Physiology, University of Rostock, Germany; 2Department of Urology, University of Rostock, Medical Center, Germany Aim: Activation of muscarinic receptors on the detrusor smooth muscle is followed by contraction, which involves both myosin light chain kinase (MLCK) and Rho kinase (ROCK). The aim of this study was to determine the relative contributions of MLCK and ROCK to carbachol-induced contraction of human detrusor smooth muscle in vitro. Methods: Detrusor smooth muscle strips were prepared from the macroscopically unaffected bladder wall of patients underwent cystectomy. The strips were fixed in an organ bath, and carbachol or KCl-induced isometric contractions were measured by force transducers. Results: Addition of carbachol (0.4-4 μmol/L) into the bath induced concentration-dependent contractions of detrusor specimens, which was completely abolished by atropine (1 μmol/L). Pre-incubation of detrusor specimens with either the MLCK inhibitor ML-9 or the ROCK inhibitors HA1100 and Y-27632 (each at 10 μmol/L) significantly blocked carbachol-induced contractions as compared to the time-control experiments. Moreover, MLCK and ROCK inhibition were equally effective in reducing carbachol-induced contractions. The residual carbachol-induced contractions in the presence of both MLCK and ROCK inhibitors were significantly smaller than the contractions obtained when only one enzyme (either MLCK or ROCK) was inhibited, suggesting an additive effect of the two kinases. Interestingly, ROCK-mediated carbachol-induced contractions were positively correlated to the age of patients (r=o.52, P